The Effect of Intermittent Theta Burst Stimulation (iTBS) in Patients With Alcohol Use Disorder: Study Protocol for a Randomized Controlled Trial - Yuan, Chenxin; Su, Hang; Chen, Tianzhen; Voon, Valerie; Du, Jiang (Frontiers in Psychiatry, 2020)
Background: Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive stimulation technique which has a treatment potential for alcohol use disorder. Intermittent Theta Burst Stimulation (iTBS) known as a new rTMS technique displays faster, more robust action, with excellent tolerability, provided that safety recommendations are followed. While the effect of iTBS on reducing craving of alcohol use disorder patients need further investigation. Methods: A randomized, controlled, single-blind, multicenter study with 60 alcohol use disorder patients randomized (2:1) to the iTBS group or the control group (sham iTBS). The stimulation target is identical in the left DLPFC. A series of evaluations will be taken before the intervention, after the intervention, and 3 months after the intervention. The primary outcome of the study will be the decrease of VAS and PACS scores from baseline to the end of treatment. Discussion: This study uses a randomized controlled trial to investigate the efficacy of leftt DLPFC iTBS in a population of alcohol use disorder patients, compared with the sham iTBS. If it is effective for alcohol use disorder, it may provide a potential treatment, and have good capacity, accessibility and clinical usefulness.